2021
DOI: 10.1200/jco.20.01814
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Sustained Minimal Residual Disease Negativity With Daratumumab-Combination Regimens in Relapsed and/or Refractory Multiple Myeloma: Analysis of POLLUX and CASTOR

Abstract: PURPOSE In relapsed and/or refractory multiple myeloma, daratumumab reduced the risk of progression or death by > 60% in POLLUX (daratumumab/lenalidomide/dexamethasone [D-Rd]) and CASTOR (daratumumab/bortezomib/dexamethasone [D-Vd]). Minimal residual disease (MRD) is a sensitive measure of disease control. Sustained MRD negativity and outcomes were evaluated in these studies. METHODS MRD was assessed via next-generation sequencing (10−5) at suspected complete response (CR), 3 and 6 months following confirme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 30 publications
5
44
0
Order By: Relevance
“… 16 MRD negativity was 15.1% in the DVd arm as compared to 1.6% in the Vd arm. 17 This study is relevant in the United States as DVd is both effective and safe for patients who relapse on lenalidomide based maintenance therapy with prior exposure but not refractoriness to PIs. Patients with lenalidomide and bortezomib refractory multiple myeloma present a highly refractory group of patients with limited options.…”
Section: Anti-cd38 Naked Antibodiesmentioning
confidence: 99%
“… 16 MRD negativity was 15.1% in the DVd arm as compared to 1.6% in the Vd arm. 17 This study is relevant in the United States as DVd is both effective and safe for patients who relapse on lenalidomide based maintenance therapy with prior exposure but not refractoriness to PIs. Patients with lenalidomide and bortezomib refractory multiple myeloma present a highly refractory group of patients with limited options.…”
Section: Anti-cd38 Naked Antibodiesmentioning
confidence: 99%
“…The SARS-CoV-2 infection and vaccination have raised concerns in complement mediated hemolytic anemias (i.e., paroxysmal nocturnal hemoglobinuria, PNH, and cold agglutinin disease, CAD), particularly if on treatment with complement inhibitors. [1][2][3] Among complement amplifying triggers (infections, traumas, and surgery 4,5 ) an emerging causative agent may be represented by SARS-CoV-2 vaccines. In PNH patients on complement inhibitors, pharmacodynamic breakthrough hemolysis (BTH) has been defined as hemolysis reactivation with hemoglobin drop due to increased complement activity.…”
Section: Conflict Of Interestsmentioning
confidence: 99%
“…Using the ongoing POLLUX and CASTOR studies in relapsed/refractory patients, an exploratory analysis has found that "Sustained MRD negativity" (defined as the maintenance of MRD negativity in bone marrow confirmed ≥ 6 or ≥12 months apart) is associated with improved PFS compared with patients who obtain MRD-negative status but not MRD dura- In addition, new relevant definitions are emerging regarding MM MRD. Using the ongoing POLLUX and CASTOR studies in relapsed/refractory patients, an exploratory analysis has found that "Sustained MRD negativity" (defined as the maintenance of MRD negativity in bone marrow confirmed ≥ 6 or ≥12 months apart) is associated with improved PFS compared with patients who obtain MRD-negative status but not MRD durability [95].…”
Section: Something New: Mrd and MM Present And Futurementioning
confidence: 99%